2006
DOI: 10.1063/1.2402913
|View full text |Cite
|
Sign up to set email alerts
|

Resonant power absorption in helicon plasma sources

Abstract: Helicon discharges produce plasmas with a density gradient across the confining magnetic field. Such plasmas can create a radial potential well for nonaxisymmetric whistlers, allowing radially localized helicon ͑RLH͒ waves. This work presents new evidence that RLH waves play a significant role in helicon plasma sources. An experimentally measured plasma density profile in an argon helicon discharge is used to calculate the rf field structure. The calculations are performed using a two-dimensional field solver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 30 publications
7
83
0
Order By: Relevance
“…The maximum value of the damping rate calculated in Ref. 9 was consistent with the experimentally measured rate. 8 Nonetheless, the conclusion of Refs.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The maximum value of the damping rate calculated in Ref. 9 was consistent with the experimentally measured rate. 8 Nonetheless, the conclusion of Refs.…”
Section: Introductionsupporting
confidence: 81%
“…The goal of Ref. 9 was to investigate this hypothesis by simulating, for the experimental plasma density profile, the rf field structure excited by the antenna. The simulation showed that the antenna indeed excited an RLH wave that formed a standing wave in the axial direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the dispersion relations ͑16͒ and ͑18͒ reveal different scalings with the axial wavenumber k z , that is, respectively, linear and quadratic scalings. The quadratic dependence of the dispersion relation ͑18͒ on the parallel wavenumber k z was observed in experiment 11 and recently also confirmed by numerical calculations 12 for the condition in which the relation ͑17͒ is fulfilled. The dependence on the radial density profile can also be deduced from computations for m = + 1 helicon mode propagation in a nonuniform plasma cylinder.…”
Section: ͑14͒mentioning
confidence: 62%
“…Boswell and Chen [2,3] have written a review of helicon research. Helicon devices use an RF power source and antenna operating between the electron and ion cyclotron frequencies to excite electromagnetic waves which damp in the region of maximum density gradient [4,5]. The layout of this first section is shown in Fig.…”
Section: Helicon Plasma Sourcementioning
confidence: 99%